Υποβρύχια έρευνα ΜΥΑ Λ.Σ.-ΕΛ.ΑΚΤ. σε Ι/Φ σκάφος που ανατράπηκε ΒΔ ν.Πάρου την 24-12-2021 (HellenicCoastguard, 2021)
: Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE